Contrasting responses of Central Asian rock glaciers to global warming - Sorg, Annina; Kääb, Andreas; Roesch, Andrea; Bigler, Christof; Stoffel, Markus (Scientific Reports, 2015)
While the responses of Tien Shan glaciers – and glaciers elsewhere – to climatic changes are becoming increasingly well understood, this is less the case for permafrost in general and for rock glaciers in particular. We use a novel approach to describe the climate sensitivity of rock glaciers and to reconstruct periods of high and low rock glacier activity in the Tien Shan since 1895. Using more than 1500 growth anomalies from 280 trees growing on rock glacier bodies, repeat aerial photography from Soviet archives and high-resolution satellite imagery, we present here the world's longest record of rock glacier movements. We also demonstrate that the rock glaciers exhibit synchronous periods of activity at decadal timescales. Despite the complex energy-balance processes on rock glaciers, periods of enhanced activity coincide with warm summers, and the annual mass balance of Tuyuksu glacier fluctuates asynchronously with rock glacier activity. At multi-decadal timescales, however, the investigated rock glaciers exhibit site-specific trends reflecting different stages of inactivation, seemingly in response to the strong increase in air temperature since the 1970s.